The effect of rational emotive therapy group counselling program in enhancing self-esteem of working students in Colegio de Sta. Rosa, Intramuros, Manila - Palackal, Treesa (Animo Repository, 1991)
This study intends to find out the effectiveness of RET Group Counseling Program in increasing the self-esteem of the working students. The experimental pretest-posttest Control group design was used in this study. The experimental group consists of eleven (11) residential working students in Colegio de Sta. Rosa, Intramuros, Manila. All of them were in high school but in different year levels. The control group consisted of ten students selected from corresponding classes with equivalent ages. The experimental group underwent twelve (12) hours RET Group Counseling whereas the control group did not. Pasao Self-Concept Scale (PSS) was used to measure their self-esteem. The data were treated by the use of T-test to find out whether a significant difference exist between the pretest and posttest results of the experimental and control groups. The T-test for independent samples were used to determine any significant difference on the post test gain scores of the expereimental and control groups on PSS. The T-test for independent samples were used. The results yielded by this study, [t=4.972 (df=10, p05)] on PSS indicate the RET Group Counseling Program was very effective in helping the working students who underwent the training to increase their self-esteem.